PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT KERUGIAN YANG DITIMBULKAN OLEH PELAKU USAHA TOKO ONLINE DI INSTAGRAM - Andre Pebrian Perdana (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
Abstract : Humans as Economicus creatures have the habit of always meeting their needs continuosly. Humans today can conduct transaction electronically (e-commerce), this make it easir for humans to buy an item. With the development of technology, an instagram application appears, in that application humans can post photos and videos, in this application online shop business actors can also offer goods to consumers online. So that this allows naughty online shop busniess actors to fool consumers who do not meet in person by providing false information statements that result in losses incurred by online shop business actors on instagram. Consumers protection is seen materially and formally as increasingly felt very important, given the increasing speed of science and technology which is the driving force for the producctivity and efficiency of producers for the goods or services they produce in order to achieve business goals. In order to pursue and achieve these two things, ultimately either directly or indirectly, it is the Consumers who generally feel the impact. The research method that will be used in journal writing is a type of research method carried out with a normative juridical approach, namelylegal principles and referring to legal norms contained in library research, namely conducting research using data form various sources such as from the Act, Bokks, Internet and Journals so that they can be assessed as revelant to the issues to be dis cussed.